2014
DOI: 10.1094/mpmi-12-13-0369-r
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals That Reactive Oxygen Species and Genes Encoding Lipid Transfer Protein Are Associated with Tobacco Hairy Root Growth and Branch Development

Abstract: The hairy root, a specialized plant tissue that emerges from a cell transformed with transfer DNA (T-DNA) from Agrobacterium rhizogenes, can be used to study root biology and utilized in biotechnological applications. The rol genes are known to participate in the generation of hairy roots; however, the means by which the rol genes contribute to the initiation and the maintenance of hairy roots remains largely unknown. We demonstrated that tobacco hairy roots lacking either rolB or rolC exhibited fewer branch r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…S8). Our observations are in line with the previously reported crucial roles of rolB and rolC in inducing hairy root formation (10,47,49,50).…”
Section: Generation Of K599 Mutant Strains Affected In Hairy Root Formationsupporting
confidence: 93%
See 1 more Smart Citation
“…S8). Our observations are in line with the previously reported crucial roles of rolB and rolC in inducing hairy root formation (10,47,49,50).…”
Section: Generation Of K599 Mutant Strains Affected In Hairy Root Formationsupporting
confidence: 93%
“…For K599, we designed sgRNAs to target the T-DNA-encoded genes rolB (B0909_24535), rolC (B0909_24530), and orf13 (B0909_24525). The Agrobacterium phenotypic plasticity (plast) genes rolB and rolC were selected because of their significant contribution to the development of the hairy root phenotype (10,47). We also included orf13, another plast gene for which the contribution to the initiation and development of hairy roots is unclear (10,48).…”
Section: Generation Of K599 Mutant Strains Affected In Hairy Root Formationmentioning
confidence: 99%
“…Upregulated proteins involved in lipid metabolism are represented by 3-ketoacyl-CoA thiolase 2 (KAT2), UDP-sulfoquinovose synthase, and short-chain dehydrogenase/reductase SDRA (Table 2). This data is consistent with Wang et al [12], who proposed a role for rolB in lipid metabolism. Interestingly, KAT2 is involved in inflorescence development by regulating peroxisomal β-oxidation [47] and benzoylated glucosinolate biosynthesis [48], i.e., KAT2 may be involved in both processes affected by rolB.…”
Section: Primary Metabolismsupporting
confidence: 93%
“…It has been shown that important ROS generators, NADPH oxidase genes AtRbohD and AtRbohF and corresponding proteins, are upregulated in rolB-expressing cells [90], and the deletion of rolB from wild-type hairy roots decreases ROS level in rolB-deficient hairy roots [12]. This data could indicate that ROS levels in rolB-transformed plants should be increased.…”
Section: Ros Metabolism and Abiotic Stress Responsementioning
confidence: 99%
“…The suppression pattern of hairy roots of NtSTOP1 -KD is very similar to that of intact roots of tobacco (Figure 2C & Supplementary Figure 2A). However, the expression patterns of the genes relating to reactive oxygen species (ROS) are different between the intact and the hairy roots, possibly because they are hairy roots [31]. Moreover, Al-tolerant cultured cells of tobacco showed Al tolerance and enhanced citrate excretion [32].…”
Section: Discussionmentioning
confidence: 99%